Clinical significance of AGE-RAGE axis in colorectal cancer: associations with glyoxalase-I, adiponectin receptor expression and prognosis - Sakellariou, Stratigoula (BMC Cancer, 2016)
BACKGROUND: Advanced glycation end products (AGEs) and their receptor RAGE emerge as important pathogenic contributors in colorectal carcinogenesis. However, their relationship to the detoxification enzyme Glyoxalase (GLO)-I and Adiponectin receptors (AdipoR1, AdipoR2) in colorectal carcinoma (CRC) is currently understudied. In the present study, we investigated the expression levels of the above molecules in CRC compared to adjacent non-tumoral tissue and their potential correlation with clinicopathological characteristics and patients’ survival. METHODS: We analyzed the immunohistochemical expression of AGE, RAGE, GLO-1, AdipoR1 and AdipoR2 in 133 primary CRC cases, focusing on GLO-I. The tumour MSI status was further assessed in mucinous carcinomas. Western immunoblotting was employed for validation of immunohistochemical data in normal and tumoral tissues as well in three CRC cell lines. An independent set of 55 patients was also used to validate the results of univariate survival analysis regarding GLO-I. RESULTS: CRC tissue showed higher intensity of both AGE and RAGE expression compared with normal colonic mucosa which was negative for GLO-I in most cases (78 %). Western immunoblotting confirmed AGE, RAGE and GLO-I overexpression in tumoral tissue. GLO-I expression was directly related to RAGE and inversely related to AGE immunolabeling. There was a trend towards higher expression of all markers (except for RAGE) in the subgroup of mucinous carcinomas which, although of borderline significance, seemed to be more prominent for AdipoR1 and AGE. Additionally, AGE, AdipoR1 and Adipo R2 expression was related to tumor grade, whereas GLO-1 and AdipoR1 to T-category. In survival analysis, AdipoR2 and GLO-I overexpression predicted shortened survival in the entire cohort and in early stage cases, an effect which for GLO-I was reproduced in the validation cohort. Moreover, GLO-I emerged as an independent prognosticator of adverse significance in the patients’ cohort. CONCLUSIONS: We herein provide novel evidence regarding the possible interactions between the components of AGE-RAGE axis, GLO-I and adiponectin receptors in CRC. AGE and AdipoR1 are possibly involved in colorectal carcinogenesis, whereas AdipoR2 and GLO-I emerged as novel independent prognostic biomarkers of adverse significance for patients with early disease stage. Further studies are warranted to extend our observations and investigate their potential therapeutic significance.